RECONFIGURING THE NIGERIAN POLITICAL SYSTEM: ISSUES AND PERSPECTIVES - Adilieje, Chuma (University of Nigeria Journal of Political Economy, 2022)
The disappearance of some structural imperatives of the compromises made by the indigenous Nigerian leaders in the process of the evolution of the Nigerian state has led to the emergence and persistence of other contradictions that continues to define the character of governance, intra-state relations and the general functioning of the Nigerian political system. In the context of the foregoing has emerged the crisis of state, in many instances occasioned by the inability of the state to remain above the clash of partisan interests. Thus, the contradictions and inadequacies of the existing political system portend danger for the sustained survival of Nigeria. This paper therefore, examines the fundamental features of the Nigerian political system, and interrogates the theoretical bases for the explanation and understanding the Nigerian political system. It establishes and highlights some of the fundamental and philosophical directions of change, most of which basically points towards the search for equity, stability, legitimacy and peaceful development in the Nigerian political system.